2018
DOI: 10.4236/jbise.2018.117015
|View full text |Cite
|
Sign up to set email alerts
|

Prevention of Avian Influenza Virus by Ultraviolet Radiation and Prediction of Outbreak by Satellite Parameters

Abstract: The present study showed that avian influenza virus (AIV) occurred in the regions with rice and wheat productions under low ultraviolet (UV) radiation while there were negligible AIV outbreaks in the regions with a high rate of skin cancer due to extensive UV radiation. It is therefore proposed that having artificial UV radiation with poultry farmhouses is a simple solution to suppress AIV outbreaks. AIV outbreaks can be predicted a few months in advance by remote sensing satellite parameters such as Cosmos (m… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

0
39
0

Year Published

2018
2018
2022
2022

Publication Types

Select...
6

Relationship

4
2

Authors

Journals

citations
Cited by 10 publications
(39 citation statements)
references
References 27 publications
(34 reference statements)
0
39
0
Order By: Relevance
“…Major aeolian dust events arise from the Sahara and Sahel deserts ("African dust"), the Australian deserts ("Australian dust"), and the Taklamakan and Gobi deserts and the Loess plateau ("Asian dust") ( Table 1 suggests that, 1) Antarctica and the Arctic have the largest surface areas of deserts in the world, which can be one of the reasons why such regions are regarded as the sources of AIV, as proposed by Kim [4]. It was revealed that habitat type influenced bacterial community of Actinobacteria and Cyanobacteria in lithobionts and surface soils from Antarctica [15].…”
Section: Aeolian Desert Dustmentioning
confidence: 99%
See 4 more Smart Citations
“…Major aeolian dust events arise from the Sahara and Sahel deserts ("African dust"), the Australian deserts ("Australian dust"), and the Taklamakan and Gobi deserts and the Loess plateau ("Asian dust") ( Table 1 suggests that, 1) Antarctica and the Arctic have the largest surface areas of deserts in the world, which can be one of the reasons why such regions are regarded as the sources of AIV, as proposed by Kim [4]. It was revealed that habitat type influenced bacterial community of Actinobacteria and Cyanobacteria in lithobionts and surface soils from Antarctica [15].…”
Section: Aeolian Desert Dustmentioning
confidence: 99%
“…Krill feed on algae while penguins feed on krill, fish, and squid. Since penguins might have starved due to the collapse of huge icebergs in the Antarctic Peninsula in 1995, it is possible that AIV carried by penguins may have been expressed due to the lack of self immunity and transmitted to the migratory birds for Continental infections (China and Mexico) of AIV in 1995 [4].…”
Section: Transmission Of Aiv With Temperaturementioning
confidence: 99%
See 3 more Smart Citations